JUSTICE AND ISLAMIC WORK ETHICS A FRAMEWORK FOR LEADERS OF PUBLIC AND PRIVATE ORGANIZATIONS - Attahiru, Mustapha Sidi (International Journal of Research -GRANTHAALAYAH, 2021)
Immorality in the public/private service has been a great concern to various governments and researchers throughout the world because of its complexity. Despite all the existing laws, rules and regulations pertaining to the public service, the policy makers have failed to arrest the situation that is multiplying day by day. This may not be unconnected with the neglect of religious ethics that control the heart of an individual as it affects the public service. Islam provides comprehensive ethical guidelines for the running of public service which can be achieved through Islamic justice and fairness. To have faithful leaders, it is of great importance for the policy makers to ensure the manifestation of religious ethics and justice in the public service through the public awareness. Using proposed methodology this paper presents a conceptual review of the leader’s work ethics based on Islamic perspectives as well as its application in modern business toward sustaining the performance of the public and private organizations. This research is significant as there is a lack of Islamic code of ethics that guides the public and private organizations effectively. There is need for empirical test in the future as this research is conceptual in nature.